Explorations in contemporary feminist literature: The battle against oppression for writers of color, lesbian and transgender communities - Pernal, Mary (P. Lang, 2002)
Explorations in Contemporary Feminist The Battle Against Oppression for Writers of Color, Lesbian and Transgender Communities is a work that bridges issues of oppression across diverse communities within the contemporary feminist movement. Fictional writings by authors such as Toni Morrison, Maya Angelou, Rose Tremain, and others are addressed in regard to their content of social messages. The major focus of this book is the need for personal-redefinition by members of marginalized communities seeking a ground of self-determination and respect, as expressed by various authors. The connections between authors' perspectives are rasied and a critical gaze is directed at the claim that personal choice equates with freedom.
Keywords: afro-féminisme; amériques; approches et analyses; arts; classisme; discipline; intersectionnalité; littérature; personnes lesbiennes; personnes trans; racisme; régions géographiques; systèmes d'oppression; états-unis; études littéraires

Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203449974
Keywords: approches et analyses; arts; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires